To what extent we do understand smart cities and characteristics influencing city smartness - Mozūriūnaitė, Skirmantė; Sabaitytė, Jolanta (Journal of Architecture and Urbanism, 2021)
Todays large cities are continually evolving human ecosystem, delivering many services to citizens. The dramatic urbanisation processes and increasing numbers of the population in cities put many strains on city infrastructure and services. XXI century urbanisation issues require robust strategies and innovative planning for their future. Easily cities are characterised as smart or intelligent without regard to clear criteria or specification for a city. There are different opinions regarding smart cities, arguing that it may bring positive social and economic change, developed governance and human capital. However, these aspects are heavily achievable without eliminating the present discrepancy in planning. The purpose of the article is to clarify and identify the characteristics of smartness based on current scholar research. The qualitative study overview on integrative literature review and seven Baltic region cities case study explores possible characteristics, and various city dimension factors which can make a city smart.